Early Childhood Education Leadership Grounded in Wetland Ecology: A Contextual Environment-Based Approach - Maimunah; Aslamiah (The Indonesian Institute of Science and Technology Research, 2026)
Principals' adaptive leadership within local ecological contexts remains an underexplored area in early childhood education (ECE) literature, particularly in regions characterized by distinctive ecosystems such as wetlands. This study aims to examine adaptive leadership practices in an Islamic ECE institution situated within the wetland ecosystem of South Kalimantan, Indonesia. Employing a qualitative approach with a single case study design, data were collected through participatory observation, in-depth interviews with the school principal, teachers, and parents, and document analysis. Inductive thematic analysis was applied, with validation conducted through source triangulation and member checking. The findings reveal three principal dimensions of adaptive leadership: first, the formulation of an institutionally religious and contextually grounded vision aligned with the wetland ecosystem; second, curriculum integration through consistent habituation strategies embedding Islamic and ecological values within daily learning activities; and third, the development of participatory community partnerships among the school, parents, and surrounding community. These three dimensions are demonstrably mutually reinforcing, collectively shaping a school culture that is religious in character, ecologically sensitive, and adaptively responsive. Theoretically, these findings extend Heifetz's adaptive leadership framework by incorporating a spiritual-ecological dimension, and enrich place-based education theory within the context of Islamic educational institutions. Practically, this study underscores the importance of designing leadership capacity-building programs that are responsive to ecological contexts and locally grounded religious values.